PREPARATIONS AND APPLICATION OF METAL NANOPARTICLES - Adlim Adlim (Indonesian Journal of Chemistry, 2006)
Terminology of metal nanoparticles, the uniqueness properties in terms of the surface atom, the quantum dot, and the magnetism are described. The further elaboration was on the synthesis of nanoparticles. Applications of metal nanoparticles in electronic, ceramic medical and catalysis were overviewed. The bibliography includes 81 references with 99% are journal articles.